SISTEM KOMPENSASI PNS BERBASIS KINERJA - Hanif, Hanif (Universitas Islam Negeri Raden Intan Lampung, 2016)
Human resource occupies a strategic position within an organization , because the human resources directly involved in the management process from the planning stage to the evaluation , therefore the policy in the field of human resources should be directed at improving the welfare of justice , in accordance with the proportion and responsibility of each employee . In achieving the objectives of the organization , human resource potential must be maximized , the achievement of organizational goals depends not only on facilities and pre means but rather depends on the performance of its human resources .Kata Kunci : Kompensasi, PNS dan Kinerja